Cooperation in Child Welfare Decision Making: Qualitative Vignette Study. Issue 2 (3rd April 2022) - Przeperski, Jaroslaw; Taylor, Brian
ABSTRACT: Many social work decisions are the outcome of collaborative working with other professionals and organisations, although there is little study of these decision-making processes. In this qualitative study conducted in Poland, the frame of reference was social work practice experience rather than a theoretical model. A vignette was presented to five respondents from each of nine groups of workers who have roles in child welfare decision making: counsellors, family assistants, family judges, family mediators, police officers, probation officers, school teachers, social workers, and voluntary probation officers. Qualitative data were gathered through interviewing respondents about the vignette. Two themes from the study related primarily to the assessment process and individual judgement prior to actual partnership engagement: " Reaching beyond the presenting problem", and " Framing the decision through problem identification" . Two other themes related to early stages of engaging with another organisation: " Clarifying responsibilities with other organisations", and " Using the diagnosis of another organization ". The fifth and final theme related to work required to help the family: " Identification of 'the one big problem'" . There seemed to be some reluctance to own responsibility for addressing a problem faced by the family. The themes were analysed using elements of risk communication and collaboration theory. The study highlights the need for leadership in partnership working built on an understanding of the realities of the practice environment and the specific responsibilities of each profession and organisation.